A 4-methyl-1-pentene polymer and preparation method thereof

Through the cascade catalytic solution polymerization technology, the preparation process of 4-methyl-1-pentene is simplified, the problems of catalyst environmental requirements and production costs are solved, and an efficient and low-cost preparation method is realized. The prepared polymer has High melting point and wide application prospects.

CN116120492BActive Publication Date: 2024-12-17QUZHOU RES INST OF ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211664921.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2024-12-17
Estimated Expiration
2042-12-23

AI Technical Summary

Technical Problem

In the existing 4-methyl-1-pentene preparation process, the catalysts are demanding environmental requirements and require supporting facilities such as separation towers, which increases industrial costs, and the storage and transportation steps are complex, which increases production costs.

Method used

Using a cascade catalytic solution polymerization technology under anhydrous and oxygen-free conditions, using transition metal or metallocene catalysts, two catalysts participate in the polymerization reaction simultaneously or sequentially in the same reactor, simplifying the separation and storage steps, and directly generating 4-A Base-1-pentene reduces equipment investment and polymerization costs.

Benefits of technology

It has achieved simplified process flow, reduced production costs, improved catalytic activity and selectivity. The prepared 4-methyl-1-pentene polymer has a high melting point and a good molecular structure, and is suitable for medical devices and LED modules. field, expanding application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a 4-methyl-1-pentene polymer and a preparation method thereof. First, propylene dimerization is carried out in a first reactor to synthesize a 4-methyl-1-pentene monomer, and then 4-methyl-1-pentene and alpha-olefin are polymerized in a second reactor to synthesize a high-melting-point 4-methyl-1-pentene polymer. The polymer prepared by the preparation method of the present invention has the characteristics of high selectivity and high melting point. The polymer prepared by the preparation method of the present invention can be used in the fields of medical devices, LED modules, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of high-performance polyolefins, and relates to a 4-methyl-1-pentene polymer and a preparation method thereof. Background Art

[0002] Polyolefins usually refer to polymers of ethylene, propylene or higher olefins, among which poly-4-methyl-1-pentene (PMP) is a new type of polyolefin material with great application potential. In addition to the excellent properties of ordinary polyolefin materials, its comprehensive properties such as high temperature resistance, electrical properties, optical properties and mechanical properties are also outstanding.

[0003] Among all transparent plastics, PMP has a light transmittance of 90-92%, the lowest refractive index, and a UV transmittance that is even better than glass and other transparent resins. Among all thermoplastics, PMP has the lowest density, only 0.83 g / cm3, and is the only semi-crystalline polymer whose crystalline phase density is lower than that of the amorphous phase. In addition, PMP has excellent electrical properties, with a dielectric constant of about 3.12, the smallest among synthetic resins. It also has high temperature resistance and oil resistance, and can be widely used in wires and cables [1]. PMP also has excellent environmental and chemical resistance, and has strong resistance to most chemicals, similar to PP, due to other polyolefin materials.

[0004] At room temperature, the mechanical properties of PMP are similar to those of polypropylene (PP). After the temperature is increased, PMP has better flexibility, elongation at break and impact strength. PMP has a high melting point, generally about 240°C, and a Vicat softening point of 173°C. Its typical processing temperature range is 270-330°C, which is higher than the operating temperature of PP. Its fluidity increases significantly with increasing temperature. Above 300°C, it is even better than the fluidity of PE and PP. Therefore, PMP has a variety of molding processing methods and can be processed on general processing equipment for thermoplastics. The most commonly used processing methods are injection molding, extrusion molding and blow molding. When processing PMP with relatively low molecular weight, injection molding is generally used due to its good fluidity; extrusion molding is generally chosen for processing PMP with relatively high molecular weight.

[0005] PMP was first synthesized by Natta of Italy using the Ziegler-Natta catalyst he invented, and semi-industrialized production was completed by ICI of the United Kingdom in 1965. Subsequently, Philips of the United States established a large-scale industrialized device with an annual output of 45 tons. Today, Mitsui Petrochemical Company of Japan is the largest producer and supplier of PMP, while my country has just started the research and development of PMP.

[0006] At present, the industrial preparation process is divided into two steps. The first is the dimerization of propylene to produce 4-methyl-1-pentene monomer. In the past, the dimerization of propylene was carried out under high temperature and high pressure using a solid catalyst prepared by loading alkaline metals such as sodium and potassium on potassium carbonate or graphite. Although a relatively mature process patent has been reported (CN111574317A), the catalyst has strict environmental requirements and requires supporting facilities such as separation towers, which increases the industrial cost. Although transition metal catalysts with mild reaction conditions can be used to reduce production costs, such as the reported uranium catalyst (US4695669A), the catalyst has great safety issues in the use environment and post-use treatment.

[0007] Secondly, in the step of copolymerization of 4-methyl-1-pentene monomer and α-olefin, the reported process is relatively mature (AU5058890A), but in this process, it is necessary to provide a suitable storage method for 4-methyl-1-pentene to improve the conservation cost of the process. Summary of the invention

[0008] The purpose of the present invention is to provide a 4-methyl-1-pentene polymer and a preparation method thereof in view of the deficiencies of existing production products and technologies.

[0009] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is:

[0010] A first aspect of an embodiment of the present invention provides a method for preparing a 4-methyl-1-pentene polymer, the method comprising the following steps:

[0011] (1) under anhydrous and oxygen-free conditions, propylene, a first catalyst, a co-catalyst and an organic solvent are added to a first reactor to undergo a polymerization reaction to obtain 4-methyl-1-pentene; the polymerization temperature is 20-120° C., and the polymerization pressure is 0.1-10 MPa; based on the volume of the solvent in the first reactor, the first catalyst is 0.1-100 μmol / L, the molar ratio of the co-catalyst to the first catalyst is 50-10000:1, and the propylene feed concentration is 0.1-20 mol / L; the residence time of all materials in the first reactor is 2-240 min;

[0012] (2) The solution after the polymerization reaction in the first reactor enters the second reactor, and under the condition of anhydrous and oxygen free, α-olefin, second catalyst, co-catalyst and organic solvent are added to the second reactor to polymerize to obtain 4-methyl-1-pentene polymer; the polymerization temperature is 50-250° C., and the polymerization pressure is 0.1-10 MPa; based on the volume of the solvent in the second reactor, the concentration of the second catalyst is 0.1-100 μmol / L, the molar ratio of the second catalyst to the first catalyst is 20:1-1:10, the molar ratio of the co-catalyst to the second catalyst is 50-10000:1, the α-olefin feed concentration is 0-5 mol / L, and the residence time of all materials in the second reactor is 2-240 min.

[0013] Furthermore, the first catalyst is a transition metal catalyst or a metallocene catalyst, selected from neutral salicylaldehyde imine nickel phosphine complex, bis(salicylidene) nickel complex, β-ketoimine nickel complex, bis(imino)pyridine vanadium (III), decamethyl-biscyclopentadienyl hafnium dichloride, nonamethyl-n-butyl-biscyclopentadienyl hafnium dichloride, octamethyl-bis(ethylcyclopentadiene) hafnium dichloride, octamethyl-bis(isobutylcyclopentadiene) hafnium dichloride.

[0014] Further, the second catalyst is a transition metal catalyst or a metallocene catalyst, selected from rac-vinylidene bridged bis-indenyl zirconium dichloride, rac-dimethylsilyl bridged-bis-indenyl zirconium dichloride, dimethylsilyl bridged-hu-yl-(tert-butylamino)-zirconium dichloride, rac-dimethylsilyl bridged-bis(2-methyl-indenyl) zirconium dichloride, rac-dimethylsilyl bridged-bis-phenylindenyl zirconium dichloride, rac-dimethylsilyl bridged-bis(2-methyl-phenylindenyl) zirconium dichloride, diphenyl carbon bridged-fluorene Dimethylsilyl-cyclopentadienyl zirconium dichloride, dimethylsilyl-(2,3-dimethyl-phenylindenyl)-tert-butylamino-titanium dichloride, dimethylsilyl-(2-methyl-phenylindenyl)-tert-butylamino-titanium dichloride, dimethylsilyl-phenylindenyl-tert-butylamino-titanium dichloride, dimethylsilyl-tetramethylcyclopentadienyl-tert-butylamino-titanium dichloride, dimethylsilyl-indenyl-tert-butylamino-titanium dichloride, dimethylsilyl-fluorenyl-tert-butylamino-titanium dichloride, pyridinyl hafnium.

[0015] Furthermore, the co-catalyst is selected from one or more of methylaluminoxane, modified methylaluminoxane, tri(pentafluorophenyl)boron compound, triisobutylaluminum, triethylaluminum, trimethylaluminum and mixed in any proportion.

[0016] Furthermore, the organic solvent is a straight-chain alkane, isoalkane, cycloalkane, aromatic alkane or a compound thereof having 4 to 10 carbon atoms.

[0017] Furthermore, the organic solvent is n-butane, n-pentane, isopentane, n-hexane, cyclohexane, n-heptane, isoheptane, n-octane, isooctane, n-decane, isoparaffin oil, toluene or xylene.

[0018] Furthermore, the α-olefin is selected from one or more of 1-butene, 1-pentene, 1-hexene, 1-octene, and 1-decene, mixed in any proportion.

[0019] A second aspect of the embodiments of the present invention provides a 4-methyl-1-pentene polymer, which is prepared by the above-mentioned preparation method of the 4-methyl-1-pentene polymer.

[0020] Furthermore, the 4-methyl-1-pentene polymer has a weight average molecular weight of 10 to 800 kg / mol, a molecular weight distribution index of 2.0 to 15.0, and an α-olefin molar content of 0 to 50%.

[0021] A third aspect of the embodiments of the present invention provides an application of a 4-methyl-1-pentene polymer obtained by the above-mentioned method for preparing a 4-methyl-1-pentene polymer in the preparation of medical devices and LED modules.

[0022] The beneficial effects of the present invention are as follows: based on the cascade continuous solution polymerization technology of the cascade metallocene catalyst system with high activity, high selectivity and high copolymerization ability, the present invention proposes a 4-methyl-1-pentene polymer and a preparation method thereof. The first catalyst used in the preparation process step 1 provided by the present invention has good catalytic activity and selectivity, and can simplify the subsequent separation operation, thereby achieving the purpose of reducing production equipment.

[0023] The present invention adopts cascade catalytic solution polymerization, which is also called bifunctional catalysis or in-situ catalysis by allowing two or more catalysts to participate in the polymerization reaction simultaneously or sequentially in the same reactor. The advantages are: 1) 4-methyl-1-pentene can be generated in-situ, eliminating the steps of separation, storage, and transportation of 4-methyl-1-pentene, simplifying the polymerization process, and reducing equipment investment and polymerization costs; 2) the polymer composition can be regulated by changing the polymerization process such as the type of catalyst, the ratio of two catalysts, and the prepolymerization time. The molar content of α-olefin in the 4-methyl-1-pentene series polymerization is 0-50%, and the crystalline part constitutes a 72-helical conformation, with high stereoregularity, high melting point, and wide molecular weight distribution. The 4-methyl-1-pentene series polymer prepared by the present invention has various possibilities for expanding the most advanced technology, and can be used in many application fields such as medical devices and LED modules. The application prospect is quite broad and has high industrial value. DETAILED DESCRIPTION

[0024] The present invention is illustrated by the following specific examples, but the scope of the present invention is not limited to the following examples.

[0025] The feed molar concentration used in the present invention refers to the initial concentration of propylene monomer when entering the reactor based on the volume of the organic solvent, and the feed molar ratio refers to the initial molar concentration ratio of propylene to ethylene monomer when entering the reactor.

[0026] The present invention provides a method for preparing a 4-methyl-1-pentene polymer, comprising the following steps:

[0027] (1) Under anhydrous and oxygen-free conditions, propylene, a first catalyst, a co-catalyst and an organic solvent are added to a first reactor to undergo a polymerization reaction to obtain 4-methyl-1-pentene; the polymerization temperature is 20-120° C. and the polymerization pressure is 0.1-10 MPa; based on the volume of the solvent in the first reactor, the first catalyst is 0.1-100 μmol / L, the molar ratio of the co-catalyst to the first catalyst is 50-10000:1, and the propylene feed concentration is 0.1-20 mol / L; the residence time of all materials in the first reactor is 2-240 min; and the selectivity of the obtained 4-methyl-1-pentene is 40%-99%.

[0028] (2) The solution after the polymerization reaction in the first reactor enters the second reactor, and under the condition of anhydrous and oxygen free, α-olefin, second catalyst, co-catalyst and organic solvent are added to the second reactor to polymerize to obtain 4-methyl-1-pentene polymer; the polymerization temperature is 50-250° C., and the polymerization pressure is 0.1-10 MPa; based on the volume of the solvent in the second reactor, the concentration of the second catalyst is 0.1-100 μmol / L, the molar ratio of the second catalyst to the first catalyst is 20:1-1:10, the molar ratio of the co-catalyst to the second catalyst is 50-10000:1, the α-olefin feed concentration is 0-5 mol / L, and the residence time of all materials in the second reactor is 2-240 min.

[0029] Wherein, the first catalyst is a transition metal catalyst or a metallocene catalyst, selected from neutral salicylaldehyde imine nickel phosphine complex, bis (salicylidene) nickel complex, β-ketoimine nickel complex, bis (imino) pyridine vanadium (III), decamethyl-bis cyclopentadienyl hafnium dichloride, nonamethyl-n-butyl-bis cyclopentadienyl hafnium dichloride, octamethyl-bis (ethylcyclopentadiene) hafnium dichloride, octamethyl-bis (isobutylcyclopentadiene) hafnium dichloride. During the reaction, the two ways of propylene molecules inserting into the metal-H bond, 1,2-insertion and 2,1-insertion, are equally likely. By adjusting the structure of the complex and the type of active center, the reaction can be more inclined to first 1,2-insertion and then 2,1-insertion, so that the main component of the six-carbon olefin is 4-methyl-1-pentene.

[0030] The second catalyst is a transition metal catalyst or a metallocene catalyst, selected from rac-vinylidene bridge bis-indenyl zirconium dichloride, rac-dimethylsilyl bridge-bis-indenyl zirconium dichloride, dimethylsilyl bridge-hu-yl-(tert-butylamino)-zirconium dichloride, rac-dimethylsilyl bridge-bis-(2-methyl-indenyl) zirconium dichloride, rac-dimethylsilyl bridge-bis-phenylindenyl zirconium dichloride, rac-dimethylsilyl bridge-bis-(2-methyl-phenylindenyl) zirconium dichloride, diphenylcarbonyl and -fluorenyl- Cyclopentadienyl zirconium dichloride, dimethylsilyl-(2,3-dimethyl-phenylindenyl)-tert-butylamino-titanium dichloride, dimethylsilyl-(2-methyl-phenylindenyl)-tert-butylamino-titanium dichloride, dimethylsilyl-phenylindenyl-tert-butylamino-titanium dichloride, dimethylsilyl-tetramethylcyclopentadienyl-tert-butylamino-titanium dichloride, dimethylsilyl-indenyl-tert-butylamino-titanium dichloride, dimethylsilyl-fluorenyl-tert-butylamino-titanium dichloride, pyridinyl hafnium. The stereocontrol of transition metal catalysts is low, resulting in poor regularity of the prepared polymers, and there is a chain walking process in the catalytic process of some transition metal catalysts, and the products are mostly amorphous polymers. The pyridinyl hafnium catalyst has a high isotactic selectivity due to the unique activation mechanism of the monomer insertion modified ligand. The structure of the metallocene catalyst has a significant effect on the isotacticity of the product. For example, the isotacticity of the product prepared by a single metallocene catalyst is relatively low.

[0031] The co-catalyst is selected from methylaluminoxane, modified methylaluminoxane, tri(pentafluorophenyl)boron compound, triisobutylaluminum, triethylaluminum, trimethylaluminum or a mixture thereof.

[0032] The organic solvent is a straight-chain alkane, isoalkane, cycloalkane, aromatic alkane or a compound thereof having 4 to 10 carbon atoms. Further, the organic solvent is preferably n-butane, n-pentane, isopentane, n-hexane, cyclohexane, n-heptane, isoheptane, n-octane, isooctane, n-decane, isoalkane oil, toluene or xylene.

[0033] The α-olefin is selected from one or more of 1-butene, 1-pentene, 1-hexene, 1-octene and 1-decene and mixed in any proportion.

[0034] Furthermore, the 4-methyl-1-pentene prepared by the above preparation method has a high selectivity, so that the 4-methyl-1-pentene polymer obtained by reacting with low-concentration hexene in the second reactor has a high melting point, which can reach 220-230°C.

[0035] Furthermore, the 4-methyl-1-pentene polymer prepared by the above preparation method has a weight average molecular weight of 10 to 800 kg / mol, a molecular weight distribution index of 2.0 to 15.0, and an α-olefin molar content of 0 to 50%.

[0036] The preparation method of 4-methyl-1-pentene polymer is described in detail below in conjunction with Examples 1 to 13. Examples 1 to 12 are two-kettle series continuous solution polymerizations, which are carried out in two 300 ml polymerization reactors; Example 13 is an intermittent solution polymerization, which is carried out in a 500 ml polymerization reactor.

[0037] Example 1

[0038] In this experiment, the first catalyst is decamethyl-biscyclopentadiene zirconium dichloride, the second catalyst is hafnium pyridylamine, the co-catalyst is methylaluminoxane, the solvent is Isopar E, and the monomers are propylene and hexene.

[0039] Before the experiment, the reactor and pipeline were cleaned with triisobutylaluminum Isopar E solution to remove impurities such as water and oxygen. The first catalyst, the second catalyst, and the co-catalyst used in the experiment were prepared into their own Isopar E solutions under nitrogen atmosphere and transferred to a storage tank for storage. The solvent Isopar E was also transferred to a storage tank for storage under nitrogen atmosphere.

[0040] The kettle 1 was heated to 30°C, the kettle 2 was heated to 50°C, the stirring speed was 1000rpm, the pressure of the kettle 1 was controlled at 22bar, and the pressure of the kettle 2 was 20bar; in the kettle 1, the concentration of the first catalyst was 20μmol / L, the concentration of the co-catalyst was 10mmol / L, the concentration of the propylene feed was 5mol / L, and the average residence time of the material in the kettle was 20min; in the kettle 2, the concentration of the second catalyst was 20μmol / L, the concentration of the co-catalyst was 20mmol / L, the concentration of the hexene feed was 0.50mol / L, and the residence time of the material in the reactor was 15min. The continuously flowing out material was washed several times with a large amount of acidified methanol, filtered and dried, and vacuum dried at 60°C for more than 8 hours.

[0041] The molecular weight (weight average Mw and number average Mn) and its distribution index (PDI) of the polymer were determined by high temperature gel permeation chromatography (PL-GPC220). 1,2,4-trichlorobenzene was used as solvent to prepare a 0.1-0.3 wt% polymer solution at 150°C, and a narrow molecular weight distribution polystyrene was used as a standard sample at 150°C, with a solvent flow rate of 1.0 ml / min. The parameters k = 5.91×10-4, α = 0.69 were used for all PS standards, and the PP parameter k = 15.6×10 -4 , α=0.76.

[0042] The melting point (Tm) of the copolymer was determined by TA Instruments Q200. 4.00-6.0 mg of the polymer sample was heated to 270°C at 10°C / min, kept constant for 5 minutes to eliminate the thermal history, then cooled to -70°C at 10°C / min, kept constant for 3 minutes, and then heated to 270°C at 10°C / min. The melting point of the polymer was obtained from the second heating curve.

[0043] The average composition of the comonomers in the copolymers was determined by carbon NMR ( 13 C NMR) was measured at 125°C, with the instrument model being Bruker AC 400. The polymer was prepared into a 10% deuterated o-dichlorobenzene solution at 150°C and pre-dissolved for 3 to 4 hours to make the sample solution uniform. The instrument parameters were optimized as follows: pulse angle 90°, reverse proton decoupling, pulse delay time 8s, collection time 1.3s, and spectrum width 8000Hz, with an average scan number of no less than 5000 times.

[0044] Example 2

[0045] The experimental conditions are as follows: after the system reaches a steady state, the concentration of the first catalyst in the kettle 1 is 5 μmol / L, the concentration of the co-catalyst methylaluminoxane is 10 mmol / L, and the other experimental conditions are the same as those in Example 1.

[0046] Example 3

[0047] The experimental conditions are as follows: after the system reaches a steady state, the concentration of the first catalyst in the kettle 1 is 90 μmol / L, the concentration of the co-catalyst methylaluminoxane is 10 mmol / L, and the other experimental conditions are the same as those in Example 1.

[0048] Example 4

[0049] The experimental conditions are as follows: after the system reaches a steady state, the concentration of the second catalyst in the kettle 2 is 90 μmol / L, the concentration of the co-catalyst methylaluminoxane is 20 mmol / L, and the other experimental conditions are the same as those in Example 1.

[0050] Example 5

[0051] The experimental conditions are as follows: after the system reaches a steady state, the concentration of the second catalyst in the kettle 2 is 10 μmol / L, the concentration of the co-catalyst methylaluminoxane is 20 mmol / L, and the other experimental conditions are the same as those in Example 1.

[0052] Example 6

[0053] The experimental conditions are as follows: after the system reaches a steady state, the concentration of the second catalyst in the kettle 2 is 10 μmol / L, the concentration of the co-catalyst methylaluminoxane is 100 mmol / L, and the other experimental conditions are the same as those in Example 1.

[0054] Example 7

[0055] The experimental conditions are as follows: after the system reaches steady state, the pressure of kettle 1 is stabilized at 12 bar, the pressure of kettle 2 is stabilized at 10 bar, the propylene feed concentration of kettle 1 is 2.72 mol / L, the hexene feed concentration of kettle 2 is 0.25 mol / L, and the other experimental conditions are the same as in Example 1.

[0056] Example 8

[0057] The experimental conditions are as follows: after the system reaches a steady state, the propylene feed concentration of kettle 1 is 18.0 mol / L, the hexene feed concentration of kettle 2 is 4.0 mol / L, and the other experimental conditions are the same as those in Example 1.

[0058] Example 9

[0059] The experimental conditions are as follows: after the system reaches a steady state, the residence time of kettle 1 is 40 minutes, and the other experimental conditions are the same as those in Example 1.

[0060] Example 10

[0061] The experimental conditions are as follows: after the system reaches a steady state, the residence time of kettle 2 is 30 minutes, and the other experimental conditions are the same as those in Example 1.

[0062] Embodiment 11

[0063] The experimental conditions are as follows: after the system reaches a steady state, the polymerization temperature of kettle 2 is maintained at 90°C, and the other experimental conditions are the same as those in Example 1.

[0064] Example 12

[0065] The experimental conditions are as follows: the second catalyst is changed to diphenyl carbon bridge group-cyclopentadienyl-pentadienyl zirconium dichloride, and the other experimental conditions are the same as those in Example 1.

[0066] Example 13 is a batch copolymerization, which is carried out in a 500 ml olefin batch polymerization reactor.

[0067] Embodiment 13

[0068] In this experiment, the first catalyst used was decamethyl-dicyclopentadiene zirconium dichloride, the second catalyst used was pyridylamine hafnium, the cocatalyst used was methylaluminoxane, the solvent was Isopar E, the monomers were propylene and hexene, and the polymerization experiment was carried out in an intermittent solution system. Before the experiment, the reactor was repeatedly evacuated and replaced with nitrogen at 100°C for 6 hours, and then evacuated and replaced with propylene three times to ensure that the entire pipeline and reactor were sealed and free of water and oxygen.

[0069] The experimental steps are as follows: first cool the reactor to 30°C and then open the liquid feed valve, add 220ml of solvent Isopar E and 10mmol of co-catalyst methylaluminoxane to the reactor, then immediately close the liquid feed valve, turn on the stirring to 1000 rpm, and after the temperature in the reactor rises to the reaction temperature, add the homopolymerization catalyst to the reactor through the pressure difference, and the pressure in the reactor quickly increases to 1.0MPa. After that, the amount of propylene consumed in the reactor during the reaction process is continuously replenished through the flow controller to ensure that the pressure in the reactor is constant. Constant temperature and constant pressure reaction for 10 minutes, then add the second catalyst to the reactor through the pressure difference, open the propylene inlet valve, continue to react for 60 minutes, close the gas feed valve, add 1-hexene to the reactor again through the pressure difference to react for 30 minutes, open the gas vent valve to release the pressure, and then open the liquid discharge valve to pour the material into a beaker filled with a large amount of acidified methanol. The polymer is filtered and washed with methanol several times, and then vacuum dried at 60°C for more than 8 hours.

[0070] In this experiment, the concentration of the first catalyst in the kettle was 5 μmol / L, the concentration of the second catalyst was 10 μmol / L, and the feed molar ratio of propylene to hexene was 10. All materials used in the experiment were treated with dehydration and deoxygenation.

[0071] Table 1. Results of cascade catalytic continuous solution copolymerization experiments

[0072]

[0073]

[0074] Note: RT18 indicates PMP industrial sample of Mitsui Co., Ltd.

[0075] As shown in Table 1 above, the present invention provides a cascade preparation method for 4-methyl-1-pentene polymers. By comparing the products of Example 1 with those of Example 13, it can be seen that the preparation method provided by the present invention can operate stably to obtain products with uniform performance. Compared with industrial samples, the product has similar performance, similar melting point and use temperature, generally has high yield strength, but low elongation. As the α-olefin content increases, the yield strength of the copolymer will decrease, but the elongation will increase. The processing temperature is between 270 and 330°C, and it can generally be processed by an injection molding machine. By simplifying the process flow, the production efficiency is improved and the polymerization cost is reduced. It has high industrial value.

[0076] Those skilled in the art will readily appreciate other embodiments of the present application after considering the description and practicing the contents disclosed herein. The present application is intended to cover any variations, uses or adaptations of the present application, which follow the general principles of the present application and include common knowledge or customary technical means in the art that are not disclosed in the present application. The description and examples are intended to be exemplary only.

[0077] It will be appreciated that the present application is not limited to the precise construction that has been described above and that various modifications and changes may be made without departing from the scope thereof.

Claims

1. A method for preparing a 4-methyl-1-pentene polymer, characterized in that: The preparation method comprises the following steps: (1) Under anhydrous and oxygen-free conditions, propylene, a first catalyst, a co-catalyst and an organic solvent are added to a first reactor to undergo a polymerization reaction to obtain 4-methyl-1-pentene; the polymerization temperature is 20-120° C., and the polymerization pressure is 0.1-10 MPa; based on the volume of the solvent in the first reactor, the first catalyst is 0.1-100 μmol / L, the molar ratio of the co-catalyst to the first catalyst is 50-10000:1, and the propylene feed concentration is 0.1-20 mol / L; the residence time of all materials in the first reactor is 2-240 min; The first catalyst is a transition metal catalyst or a metallocene catalyst, selected from neutral salicylaldehyde imine nickel phosphine complex, bis(salicylidene) nickel complex, β-ketoimine nickel complex, bis(imino)pyridine vanadium(III), decamethyl-biscyclopentadienyl hafnium dichloride, nonamethyl-n-butyl-biscyclopentadienyl hafnium dichloride, octamethyl-bis(ethylcyclopentadiene) hafnium dichloride, octamethyl-bis(isobutylcyclopentadiene) hafnium dichloride; (2) The solution after the polymerization reaction in the first reactor enters the second reactor, and under the condition of anhydrous and oxygen-free, α-olefin, a second catalyst, a co-catalyst and an organic solvent are added to the second reactor to polymerize to obtain 4-methyl-1-pentene polymer; the second catalyst is a transition metal catalyst or a metallocene catalyst; the polymerization temperature is 50-250° C., and the polymerization pressure is 0.1-10 MPa; based on the volume of the solvent in the second reactor, the concentration of the second catalyst is 0.1-100 μmol / L, the molar ratio of the second catalyst to the first catalyst is 20:1-1:10, the molar ratio of the co-catalyst to the second catalyst is 50-10000:1, the α-olefin feed concentration is 0-5 mol / L, and the residence time of all materials in the second reactor is 2-240 min; The second catalyst is selected from rac-vinylidene bridged bis-indenyl zirconium dichloride, rac-dimethylsilyl bridged-bis-indenyl zirconium dichloride, dimethylsilyl bridged-fluorenyl-(tert-butylamino)-zirconium dichloride, rac-dimethylsilyl bridged-bis(2-methyl-indenyl) zirconium dichloride, rac-dimethylsilyl bridged-bis-phenylindenyl zirconium dichloride, rac-dimethylsilyl bridged-bis(2-methyl-phenylindenyl) zirconium dichloride, diphenylcarbon bridged-fluorenyl-cyclopentadienyl zirconium dichloride. , dimethylsilyl-(2,3-dimethyl-phenylindenyl)-tert-butylamino-titanium dichloride, dimethylsilyl-(2-methyl-phenylindenyl)-tert-butylamino-titanium dichloride, dimethylsilyl-phenylindenyl-tert-butylamino-titanium dichloride, dimethylsilyl-tetramethylcyclopentadienyl-tert-butylamino-titanium dichloride, dimethylsilyl-indenyl-tert-butylamino-titanium dichloride, dimethylsilyl-fluorenyl-tert-butylamino-titanium dichloride, pyridinyl hafnium.

2. The method for preparing a 4-methyl-1-pentene polymer according to claim 1, characterized in that: The co-catalyst is selected from one or more of methylaluminoxane, modified methylaluminoxane, tri(pentafluorophenyl)boron compound, triisobutylaluminum, triethylaluminum, trimethylaluminum and mixed in any proportion.

3. The method for preparing a 4-methyl-1-pentene polymer according to claim 1, characterized in that: The organic solvent is a straight-chain alkane, isoalkane, cycloalkane, aromatic alkane or a compound thereof having 4 to 10 carbon atoms.

4. The method for preparing a 4-methyl-1-pentene polymer according to claim 3, characterized in that: The organic solvent is n-butane, n-pentane, isopentane, n-hexane, cyclohexane, n-heptane, isoheptane, n-octane, isooctane, n-decane, isoparaffin oil, toluene or xylene.

5. The method for preparing a 4-methyl-1-pentene polymer according to claim 1, characterized in that: The α-olefin is selected from one or more of 1-butene, 1-pentene, 1-hexene, 1-octene and 1-decene and mixed in any proportion.

6. A 4-methyl-1-pentene polymer, characterized in that The 4-methyl-1-pentene polymer is prepared by the preparation method of any one of claims 1 to 5.

7. A 4-methyl-1-pentene polymer according to claim 6, characterized in that: The 4-methyl-1-pentene polymer has a weight average molecular weight of 10 to 800 kg / mol, a molecular weight distribution index of 2.0 to 15.0, and an α-olefin molar content of 0 to 50%.

8. Use of a 4-methyl-1-pentene polymer prepared by the method for preparing a 4-methyl-1-pentene polymer according to any one of claims 1 to 5 in preparing medical devices and LED modules.